2015
DOI: 10.1021/acs.molpharmaceut.5b00333
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Strength of Drug–Polymer Interactions on the Molecular Mobility and Crystallization Inhibition in Ketoconazole Solid Dispersions

Abstract: The effects of specific drug-polymer interactions (ionic or hydrogen-bonding) on the molecular mobility of model amorphous solid dispersions (ASDs) were investigated. ASDs of ketoconazole (KTZ), a weakly basic drug, with each of poly(acrylic acid) (PAA), poly(2-hydroxyethyl methacrylate) (PHEMA), and polyvinylpyrrolidone (PVP) were prepared. Drug-polymer interactions in the ASDs were evaluated by infrared and solid-state NMR, the molecular mobility quantified by dielectric spectroscopy, and crystallization ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
188
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(202 citation statements)
references
References 53 publications
(128 reference statements)
13
188
0
Order By: Relevance
“…Similar results were obtained in a study on felopidine ASDs in which an inverse correlation between the strength and extent of H bonding between API and polymer (as judged from the IR data) and crystal growth was established [214]. Drug-polymer interactions in ASDs of ketoconazole were also evaluated by IR and solid-state NMR spectroscopy and correlated to the molecular mobility and crystallization onset [215]. Démuth et al used Raman mapping to evaluate the longterm stability of itraconazole ASDs prepared by electrospinning [216].…”
Section: Savolainen Et Al Reported An Example Where In Situsupporting
confidence: 76%
“…Similar results were obtained in a study on felopidine ASDs in which an inverse correlation between the strength and extent of H bonding between API and polymer (as judged from the IR data) and crystal growth was established [214]. Drug-polymer interactions in ASDs of ketoconazole were also evaluated by IR and solid-state NMR spectroscopy and correlated to the molecular mobility and crystallization onset [215]. Démuth et al used Raman mapping to evaluate the longterm stability of itraconazole ASDs prepared by electrospinning [216].…”
Section: Savolainen Et Al Reported An Example Where In Situsupporting
confidence: 76%
“…For example, the C-H stretching and C ¼ N stretching were shortened and broadened and the shallow peak of N-H stretching also demonstrated shifting to 3394 cm À1 instead of 3217 cm À1 (Figure 3). These results strongly suggest that the interaction between OL and ascorbic acid may have taken place through H-bonding (Mistry et al, 2015).…”
Section: Discussionmentioning
confidence: 68%
“…Mistry et al have also shown that stronger drug-polymer interactions (ionic or H-bonding) reduce the molecular motion of amorphous ketoconazole which can potentially delay crystallization onset time and reduce crystallization extent. 126 In another interesting study conducted by Kothari et al 127 it has been found that the relaxation time of the drug increases with an increase in polymer concentration. The improved stability results were attributed to the restriction of molecular mobility of amorphous drug.…”
Section: Reduction Of Molecular Mobility Of Amorphous Drug In Pasdmentioning
confidence: 94%